Efektivitas Inisiasi Menyusu Dini (Imd) Terhadap Keberhasilan Pemberian Asi Eksklusif - Happy Tri K. Hura; Erlina Septiniati Gulo (CV. SINAR HOWUHOWU, 2026)
Early Breastfeeding Initiation (EBI) is one of the key interventions recommended by the World Health Organization (WHO) to improve the success of exclusive breastfeeding. EBI within the first hour after birth is believed to stimulate lactation, strengthen mother–infant bonding, and support the continuity of breastfeeding practices. This study aimed to analyze the effectiveness of Early Breastfeeding Initiation (EBI) on the success of exclusive breastfeeding based on published research findings. This study employed a literature review approach by examining scientific articles retrieved from Google Scholar, PubMed, ScienceDirect, and Garuda databases. The reviewed articles were published between 2016 and 2026 and discussed the relationship between EBI and exclusive breastfeeding success. Articles were selected based on predetermined inclusion and exclusion criteria and analyzed narratively to synthesize the findings. Most studies reported a positive and significant relationship between EBI implementation and the success of exclusive breastfeeding. Infants who received EBI within the first hour of life were more likely to be exclusively breastfed for the first six months than those who did not receive EBI. Factors supporting successful EBI included healthcare provider support, vaginal delivery, adequate maternal knowledge, and family support, while cesarean delivery, lack of education, and prelacteal feeding practices were identified as barriers. Early Breastfeeding Initiation is effective in improving the success of exclusive breastfeeding. Optimizing EBI implementation through maternal education, family support, healthcare provider competency enhancement, and supportive health facility policies is essential to increase exclusive breastfeeding coverage and improve infant health outcomes.